Life cycle management of concrete structures based on sustainability indicators - Hiroshi Yokota; Kohei Nagai; Koji Sakai (Acta Polytechnica CTU Proceedings, 2022)
A concrete structure should be sufficiently planned, designed, executed and maintained to ensure its requirements during the life cycle. However, structures suffering from serious deterioration in structural members and sometimes subsequent loss in sustainability have been often found due to various reasons. One of the reasons is lack of total management for the structure. To meet these facts, it is extremely important to pursue coordination of engineering work in the design, execution and maintenance stages. The life cycle management is an organized system to support engineers decision to realize sufficient sustainability of the structure in the design, execution, maintenance, and all related work during its life cycle. The life cycle management is implemented based according to the life cycle management scenario in which balance of several sustainability indicators should be considered with ensuring overall sustainability. The sustainability indicators will be determined from the social, environmental and economic points of view. The scenario should be regularly reviewed based on the PDCA cycle and be updated if necessary. This paper deals with the concept and framework of the life cycle management of concrete structures to ensure sustainability during the structural life.